THE LEGAL PROTECTION FOR VICTIMS OF CRIMINAL ACTS IN BINOMO TRADING FRAUD: (Case Study on Decision Number: 1240/PID.SUS/2022/PN.TNG) - Bayu Butar Butar; Ahmad Sudiro (Transpublika Publisher, 2024)
The objective of this study is to analyze the recovery of assets and the protection of victims in cases of Binomo trading fraud under Indonesian criminal law. The research methodology employed is normative legal research, utilizing a literature-based approach. The findings of this study reveal that the decision made by the Panel of Judges in case number 1240: Pid.Sus/2022/PN.Tng was deemed unjust for the victims, leading to an appeal hearing resulting in decision number 117/Pid.Sus/2022/PT.BTN. According to this court decision, the confiscated evidence in the Indra Kenz case was to be returned to the victims through the United Indonesian Traders Association. However, the process of returning the evidence encountered complications due to internal conflicts among the victim association members. As a result, there is currently no clarity regarding the completion of the restitution of the victims' losses. The government, through the LPSK, regulates the restitution of victims' losses as stipulated in Perma Number 1 of 2022. Nevertheless, the LPSK is not involved in the process of returning the victims' losses, which is instead handled by the United Indonesian Traders Association.